Procedure to Improve the Confidence in the Selection of Design Equipment Subcontractors by Implementing Set Based Design (SBD) and Choosing by Advantages (CBA) Methodologies in Multifamily Building Projects - Celestino Romero, Milagros (2025)
The selection process of design team subcontractors by real estate companies is crucial in construction projects, directly affecting the quality and efficiency of the final results. However, the lack of time to evaluate potential subcontractors can lead to inadequate selection and negatively impact the project development. This study proposes an innovative approach to improve confidence in the selection processes of design team subcontractors in multifamily building projects by implementing Set Based Design (SBD) and Choosing by Advantages (CBA) methodologies. These methodologies, supported by Excel Macros programming and data visualization in Power BI, aim to automate and optimize the selection process, reducing human intervention. The study follows these steps: (1) information registration and analysis by experts, (2) determination of the conventional subcontract selection process in the evaluated projects, (3) development of a new selection process based on SBD and CBA, and (4) implementation of this new process through Excel Macros programming applying SBD and CBA. The integration of SBD and CBA seeks to improve the transparency, reliability, and efficiency of the process, facilitating faster and more informed decisions. The results of the study show a 36% improvement in the confidence index, demonstrating the efficiency of the selection process. These findings support the automation of the selection process and highlight its contribution to a more accurate and efficient selection of subcontractors.